Confirming Pathogenicity of the F386L PSEN1 Variant in a South Asian Family With Early-Onset Alzheimer Disease. (7th February 2022) - Eger, Sarah J.; Le Guen, Yann; Khan, Raiyan R.; Hall, Jacob N.; Kennedy, Gabriel; Zaharchuk, Greg; Couthouis, Julien; Brooks, William S.; Velakoulis, Dennis; Napolioni, Valerio; Belloy, Michaël E.; Dalgard, Clifton L.; et al.
Abstract : Objectives: The F386L PSEN1 variant has been reported in 1 Japanese family with limited clinical information. We aimed to prove that F386L is pathogenic by demonstrating that it segregates with early-onset Alzheimer disease (AD). Methods: Eight individuals in a South Asian family provided DNA for genetic testing and underwent a neurologic examination. Results: The female proband was diagnosed with AD at age 45 years and died at age 49 years. She had a CSF biomarker profile consistent with AD, and her florbetaben PET scan was amyloid positive with high uptake in the striatum. Her MRI showed no prominent white matter disease. Her affected relatives had an age at onset range of 38–57 years and had imaging and biomarker profiles similar to hers. Discussion: The results presented here, in conjunction with the prior report, confirm the pathogenicity of F386L. Furthermore, our study highlights the importance of studying families from underrepresented populations to identify or confirm the pathogenicity of rare variants that may be specific to certain genetic ancestries.